SweetGAINS project Speed Breed and Seed Community of Practice-West Africa virtual meeting report (27,29 May; 1,3,5 June 2020) - International Potato Center (International Potato Center, 2020)
The SweetGAINS SpeedBreed and Seed CoP - West Africa virtual meeting was held on 27 and 29 May and 1, 3 and 5 June 2020. The meeting aimed to ensure the continuing development and dissemination of nutritious and productive sweetpotato varieties for West Africa. The meetings were organized by CIP under the SweetGAINS project and aligned to CORAF’s priority regional programs like the National Centers of Specialization [NCoS] and Regional Centers of Excellence [RCoE]). The meeting objectives were: to work towards building a functioning regional sweetpotato Breeding and Seed CoP in West Africa; and to strengthen the capacity of interested partner programs in key elements of breeding excellence, including product profiles, stage gate management, trial design and data management. The meeting was attended by 33 participants (10 female; 23 male) from several national agricultural programs in the ECOWAS region, including Burkina Faso, Cote d’Ivoire, Ghana, Mali, Nigeria, Senegal, Sierra Leone, and Togo. The participants included breeders, agronomists, economists, social scientists and program managers.